1999
DOI: 10.1159/000016321
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Cation Channels in the Heart and Cells of the Cardiovascular System

Abstract: In many nonexcitable cells, activation of phospholipase C (PLC)-linked receptors results in a release of Ca2+ from intracellular stores followed by a transmembrane Ca2+ entry. This Ca2+ entry underlies the sustained phase of [Ca2+]i increase, is important for various cellular functions including gene expression, secretion and cell proliferation, and is supported by agonist-activated Ca2+-permeable ion channels. Ca2+-permeable channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 112 publications
0
47
0
Order By: Relevance
“…These results suggest that increased Ca 2+ influx by LTCCs was pathologic, consistent with our results here showing exacerbated hypertrophy following TAC stimulation or isoproterenol infusion in β2a DTG mice (Supplemental Figure 3). Similarly, increased Ca 2+ influx in myocytes through transient receptor potential canonical (TRPC) channels, which mediate store-, receptor-, and stretch-operated Ca 2+ entry (28)(29)(30)(31), can induce pathologic hypertrophy through a calcineurin-dependent pathway (32)(33)(34). Similarly, we have shown that overexpression of PMCA4b, which presumably removes Ca 2+ from defined sarcolemmal microdomains involved in signaling to calcineurin, could reduce the cardiac hypertrophic response (9).…”
Section: Discussionmentioning
confidence: 80%
“…These results suggest that increased Ca 2+ influx by LTCCs was pathologic, consistent with our results here showing exacerbated hypertrophy following TAC stimulation or isoproterenol infusion in β2a DTG mice (Supplemental Figure 3). Similarly, increased Ca 2+ influx in myocytes through transient receptor potential canonical (TRPC) channels, which mediate store-, receptor-, and stretch-operated Ca 2+ entry (28)(29)(30)(31), can induce pathologic hypertrophy through a calcineurin-dependent pathway (32)(33)(34). Similarly, we have shown that overexpression of PMCA4b, which presumably removes Ca 2+ from defined sarcolemmal microdomains involved in signaling to calcineurin, could reduce the cardiac hypertrophic response (9).…”
Section: Discussionmentioning
confidence: 80%
“…Voltage-independent SOC channels are sensitive to changes in SR Ca 2ϩ content and are activated upon SR depletion. TRPC gene products have been suggested as potential underlying components of native SOC in the cardiovascular system (16,39,43). TRPC1, TRPC4, and TRPC6 figure prominently as components of native SOC in pulmonary VSMC and endothelial cells and are involved in regulating vascular tone, microvascular permeability, and cell proliferation (5,13,17,21,33,40,61,62,68,70,72).…”
Section: Discussionmentioning
confidence: 99%
“…Specific primers for mTRPC1, mTRPC2, mTRPC3, mTRPC4, mTRPC5, mTRPC6, and mTRPC7 were used for PCR amplification, respectively. 19 To control for potential genomic DNA contamination, a cDNA reaction was performed but in the absence of reverse transcriptase and used as template for PCR reactions. …”
mentioning
confidence: 99%